The Influence of Job Stress and Motivation on Job Satisfaction of Bone Regency PDAM Employees - Hasmariani; Agus Salim HR; Sitti Marhumi (Income Journal Of Economics Development, 2024)
The aim of this research is a type of quantitative research with the aim of finding out the effect of work stress and motivation on job satisfaction of PDAM Bone Regency employees. This sample was taken from the Bone Regency PDAM office. The type of data used in this research is quantitative data obtained from distributed questionnaires and is related to the problem being studied. Data collection was carried out by observation and distribution of questionnaires. In this research, the data sources used in data collection include primary data and secondary data. The research instrument used in this research used the Likert scale method. Based on the results of data research using statistical calculations through the Statistical Package for the Social Science (SPSS) version 29 application regarding the influence of work stress and motivation on job satisfaction of Local Water Company (PDAM )Bone Regency employees which was discussed in the previous chapter, the author draws important conclusions, namely work stress and Motivation has a positive and significant effect on employee job satisfaction. Existing work stress and motivation must be further improved and maintained because it can be seen from the. The results of the research are data obtained in research on job satisfaction of employees of the Regional Drinking Water Company (PDAM) of Bone Regency. Based on the results of the t test, it can be concluded that the work stress variable (X1) has a positive and significant effect on job satisfaction of employees of the Regional Drinking Water Company (PDAM) of the Regency. Bone, and Work Motivation also have a positive and significant effect on job satisfaction of employees of the Regional Drinking Water Company (PDAM) of Bone Regency.research results that existing work stress is still quite normal and stable.